TaisÄ«r Taâ€˜lÄ«m MahÄrat al-KalÄm - Ubaidillah, Ubaidillah (Universitas Islam Negeri Walisongo Semarang - Indonesia, 2019)
Speech is the most important means of social communication in humans, and therefore is the most important part in the practice and use of language and the most dangerous skill of the four skills, which makes the teaching of speech, conversation, and oral communication is essential should be paid attention within the curriculum of language teaching, in order to enable learners to acquire the skills of speech and speech Constructive discussion and the ability to express and display information and the possibility of introducing himself and his intellectual activity to colleagues, family and teachers and express himself when he communicates with others and others. Given the importance of this skill and the seriousness of its place in the framework of language teaching on the one hand, and poor care in the reality of teaching Arabic language, especially Indonesia, on the other hand, this little research seeks to introduce the idea in facilitating the teaching of speech skill and its introductory attempts, which include theoretical and practical aspects to achieve this goal, By evaluating the reality of speech skill in the methods of language teaching and the attention it receives from all these methods and bring the steps of teaching this skill in an appropriate manner taking into account the communicative applications in its education and address the weakness of learners.